Measuring the severity of injury. - Stoner, H B (1977)
The injury severity score as a method for measuring the severity of injury has been found useful for epidemiological and metabolic research. Comparison with plasma cortisol concentrations confirmed that the method could distinguish between minor and moderate injuries. Before using the method one must decide on the need to weight the score for age. This is necessary when studying some relationships--for example, mortality and severity--but not others--for example, plasma cortisol concentration and severity.